Promoting Learners' Autonomy in Modern Era: A Textbook Analysis Under the Zone of Proximal Development Approach - Ilham, Dodi; Pirol, Abdul; Baderiah, Baderiah; Iksan, Muhammad; Efendi, Erwatul; Zainuddin, Andi Husni A.; Alam, Samsu (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palopo), 2024)
This research aims to explore the integration of Lev Vygotsky's Zone of Proximal Development (ZPD) theory in the context of Islamic Religious Education (IRE) and character-building, focusing particularly on fostering student autonomy. The study addresses the need for a more holistic educational approach in IRE and character-building, which emphasizes transmitting religious knowledge and values and cultivates essential life skills like independence. This literature study employs qualitative descriptive methods, analyzes learning materials in IRE and character-building textbooks, and evaluates how these materials support students in their ZPD. Results indicate that this education is crucial in instilling honest, responsible, and independent behavior involving physical, economic, intellectual, moral decision-making, and spiritual aspects. However, several sub-indicators of independence are not yet fully integrated into the curriculum, indicating room for further development. Applying ZPD in learning depicts a dynamic and interactive approach, with teachers acting as active facilitators. This research highlights the need for IRE and character-building teachers to utilize ZPD to enhance student understanding and independence, focusing on the practical application of Islamic values in daily life. This study opens new insights in Islamic education literature, emphasizing significant and applicable learning, and supports the development of independent individuals, both in action and belief. Consequently, this education reinforces the internalization of religious and moral values, shaping competent and independent individuals in modern society.